HOMONYMY IN THE FORMATION OF RUSSIAN AND VIETNAMESE COMPOUND NOUNS (Journal of Foreign Language Studies, 2019)
In the formation of compound nouns in the Russian and Vietnamese languages, there are phenomena connected with mutual morphological-semantic relations between components of a compound noun. One of such phenomena is homonymy.In the Russian language, homonymy takes place when different components of compound words have identical phonemic form (spelled alike) but express different meanings; or different meanings of different components have identical phonemic form. The homonymy in the formation of Russian compound words involves: homonymy of components of compound words (homonymy of subordinate components and homonymy of main components) and homonymy of the whole compound words.In Vietnamese, there are many homonyms that act as components of compound nouns. The pairs (or series) of compound nouns that are homonyms may consist of (1) Vietnamese words, or (2) a Vietnamese word and a Sino-Vietnamese word, or (3) two Sino-Vietnamese words.In both the Russian and Vietnamese languages, components of compound nouns (both subordinate and main components) are often homonyms, while homonymy is rarely found in the whole compound words.
Keywords: word-formation; homonymy; word-formative homonymy; compound nouns